(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
This article develops the basics of the theory of harmonious construction of complex words in the Ukrainian language on the principles of the concept of “golden” proportions. A hypothesis about their harmony on the phonetic (acoustic) levels is put forward. It is proved that the harmonic construction of yuktaposites should be considered as the ordering of components of such nominations by a certain system of perfect relations, the basic among which is the proportion that divides the corresponding division of the whole into two parts and is called “golden”. The main provisions of the methodology of the study of the harmonic construction of yuksastoposits are formulated on the example of the “golden proportion” as the laws of the universe. It is proposed to evaluate the harmonious construction of complex nominations with the help of the linguistic-informative approach. This approach involves combining the foundations of the linguistic theory of word-formation and some of the provisions of the theory of information of modern computer technologies and makes it possible to study the patterns of harmonic yukstаposites at the phonetic (acoustic) level. Quantitative indicators of harmony are systematized with the help of families of “golden” p- and S-proportions, as well as p-numbers of Fibonacci, which should be used in the analysis of the regularities of the structural organization of complex words. The notion of their linguistic redundancy is introduced, the level of which determines the parameters p and S. It is proved that the presence in the construction of yuksastopositov at the fatematic level of welldefined harmonic proportions and time relations is logical. This is due to the fact that the mechanism of human brain directly affects the process of forming the language as a means of human communication in general and the emergence of complex nominations. In the process of word formation, the human brain flexibly solves the problem of “constructing” complex nominations that would be harmonious, in particular, “convenient” and “beautiful”.